Developing Visual Basic-Based Science Learning Media Technology at SDN I Telukjambe Karawang - Jajuli, Mohammad; Hidayat, Rahmat; Kurniawan, Adit; Juanda, Enjang Ahmad (International Conference on Elementary Education, 2022)
The results of observations that have been carried out at SDN Telukjambe I Karawang show that there are main problems related to science learning. The problems are caused by the lack of studentsâ€™ motivation in learning because the learning process is too monotonous at school, and the use of learning media is not optimal in supporting teaching and learning activities. The purpose of this research is to develop visual basic-based science learning media. This study is a research and development method. The research design consists of five stages, namely problem analysis, product development planning, product development, product revision, and final product. The first step is to analyze the problem of science learning. The second stage is developing science learning media by analyzing core competency standards and basic competencies based on the curriculum. The third stage is developing visual basic-based science learning media to be shown to students. The fourth stage is validating material and media by experts. Use of visual basic-based science learning media can encourage students' motivation in understanding the learning. The feasibility of visual basic-based Science learning media was obtained from the results of the assessment of the experts in media and materials that mostly obtained â€œgoodâ€ criteria.